1995
DOI: 10.1080/02652039509374358
|View full text |Cite
|
Sign up to set email alerts
|

Natural occurrence of acetylated derivatives of deoxynivalenol and nivalenol in wheat and barley in Japan

Abstract: Thirty-four samples of domestic wheat and barley grains, collected from eight prefectures of different locations in Japan and previously determined to be positive for deoxynivalenol (DON), nivalenol (NIV) and/or zearalenone (ZEA), were analysed for acetylated derivatives of DON and NIV by gas chromatography-mass spectrometry. In addition to DON and NIV, 3-acetyldeoxynivalenol (3-ADON), 15-acetyldeoxynivalenol (15-ADON) and 4-acetylnivalenol (4-ANIV) were found in 25, 4 and 14 samples, respectively. A regional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(40 citation statements)
references
References 22 publications
1
39
0
Order By: Relevance
“…There are no regulations regarding NIV anywhere in the world, but NIV has higher toxicity than DON, and in Japan there are several reports regarding cereal contamination by NIV. 2,18,25) This fact prompted us to measure NIV in addition to DON. Our ELISA kit is the first method capable of determining the concentration of NIV, precisely and it can be used to screen NIV-contaminated materials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are no regulations regarding NIV anywhere in the world, but NIV has higher toxicity than DON, and in Japan there are several reports regarding cereal contamination by NIV. 2,18,25) This fact prompted us to measure NIV in addition to DON. Our ELISA kit is the first method capable of determining the concentration of NIV, precisely and it can be used to screen NIV-contaminated materials.…”
Section: Discussionmentioning
confidence: 99%
“…16,17) Toxic derivatives of trichothecene mycotoxins are known to exist. 18) Therefore in order to quantify the degree of trichothecene mycotoxin contamination, it is best to measuring unclear the derivatives collectively rather than individually. Nevertheless, it is also important to determine the three major trichothecene mycotoxins, DON, NlV, and T-2, individually.…”
Section: A Practical Methods For Measuring Deoxynivalenol Nivalenol mentioning
confidence: 99%
“…Differences in the geographical distribution of DON and NIV chemotypes of F. gramineraum have been reported. Only the DON chemotype has been found in the United States and Canada (16), while both chemotypes were isolated in Japan (26), Italy (14), South Africa (23), and Australia (2). Successively, Sugiura et al (22) demonstrated that some G. zeae isolated from rice stubble in Japan produced both NIV and DON.…”
Section: Introductionmentioning
confidence: 99%
“…The Fusarium fungi are commonly found on cereals grown in the temperate regions of America, Europe and Asia. In Japan, nivalenol contamination of wheat and barley is as prevalent as that of deoxynivalenol, another trichothecene mycotoxin 13,17 . Although the acute toxicity of nivalenol is thought to be equivalent to or more potent than that of deoxynivalenol, the paucity of reports suggests that nivalenol has garnered far less interest than deoxynivalenol.…”
Section: Introductionmentioning
confidence: 99%